Mechanically induced single-molecule helicity switching of graphene-nanoribbon-fused helicene on Au(111). Issue 40 (22nd September 2021) - Ishii, Ayumu; Shiotari, Akitoshi; Sugimoto, Yoshiaki
Abstract : Graphene nanoribbon-fused helicene was fabricated via on-surface synthesis. The helicity of the product was reversibly switchable by pushing a CO-terminated scanning-probe-microscopy tip into the protruding helical terminal. Abstract : Helicene is a functional material with chirality caused by its characteristic helical geometry. The inversion of its helicity by external stimuli is a challenging task in the advanced control of the molecular chirality. This study fabricated a novel helical molecule, specifically a pentahelicene-analogue twisted aromatic hydrocarbon fused with a graphene nanoribbon, via on-surface synthesis using multiple precursors. Noncontact atomic force microscopy imaging with high spatial resolution confirmed the helicity of the reaction products. The helicity was geometrically converted by pushing a CO-terminated tip into the twisted framework, which is the first demonstration of helicity switching at the single-molecule scale.